A Conceptual Review of the Physical Aspect in Expressing Children’s Character and Interest in Social Studies Learning in MI/SD - Susilasari; Aramudin (Widya Accarya, 2026)
This study presents a conceptual synthesis of the role of physical characteristics such as facial expressions, body gestures, voice intonation, and behavioral attitudes in children’s interactions during Social Studies learning in MI/SD. The study employs a literature review approach, focusing on collecting, examining, and synthesizing relevant scholarly sources to develop a comprehensive conceptual understanding of the topic. Rather than establishing causal relationships, this review explores how various physical indicators are interpreted within educational contexts and how they are conceptually associated with children’s character expression and learning interest. The synthesis of the literature suggests that different physical cues may be understood as meaningful representations in the learning process. For instance, hand gestures are often conceptually linked to motor engagement and social interaction, while fingerprints are occasionally discussed in relation to individual cognitive tendencies in a symbolic manner. Similarly, nails and hair are sometimes interpreted as reflecting emotional states and personality-related aspects. Facial expressions and eye behavior are commonly associated with attention and motivational engagement, whereas cognitive indicators such as thought patterns are inferred through observable learning behaviors. However, these interpretations remain largely theoretical and context-dependent. This conceptual review is limited by its reliance on secondary sources and the absence of empirical validation. Therefore, the findings should be understood as interpretative frameworks rather than definitive conclusions. Overall, the study highlights the importance of considering physical and behavioral cues as part of a broader pedagogical perspective that may support more responsive and inclusive Social Studies learning in elementary education.